THE IMPORTANCE OF FORMING LEGAL AWARENESS AND LEGAL CULTURE IN SOCIETY - Ashuroxunova, Iroda Toxir qizi (INTERNATIONAL CONFERENCES, 2022)
This article discusses law, legal consciousness, the structure of legal consciousness, its components, legal culture, legal ideology and legal mentality, as well as the impact of these categories on the development of society.